Implementasi Intelligent IoT Gateway Sebagai Pengendali Jarak Jauh Pada Raspberry Pi Berbasis OpenWrt - Dhito Aji Tri Prabowo; Marsekal Dadrian Setyayudha; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
Internet of Things is a concept where a particular object has a function to transfer data through wireless networks and the internet as a remote controller, this activity does not require interaction from human to human or human to computer. Everything has been run automatically with the program. Internet of Things is commonly called IoT. By implementing IoT at home it is hoped that it can improve efficiency and comfort for the occupants of the house. The smart home system that will be made has two main elements, namely an Android-based smart phone device and an automation system that has been installed on a Raspberry-Pi that has OpenWrt firmware installed and is connected directly to the relay. The system will also be equipped with an ACS712 current sensor and a ZMPT101B voltage sensor, the two devices are used to obtain electrical voltage data which will then be stored in storage on the router. After testing using AVOmeter, the data difference is relatively small. The error rate of the voltage gauge is 4.1% on average and the error rate of the current sensor is 6.2%. Data from the electricity load will be displayed on the application on an Android-based smart phone device. The results of this study are a remote control system for devices connected to electricity and provide information to analyze the use of electrical loads at home, so they can choose devices that should not be activated by the system so as to cut monthly electricity costs